1998
DOI: 10.1074/jbc.273.10.5607
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Activation of the UDP-Glucuronosyltransferase1A7 Gene in Rat Liver by Aryl Hydrocarbon Receptor Ligands and Oltipraz

Abstract: UDP-glucuronosyltransferase UGT1A7 catalyzes the glucuronidation of benzo(a)pyrene metabolites and other bulky aromatic compounds. Both UGT1A7 mRNA and an associated enzyme activity (benzo(a)pyrene-7,8-dihydrodioltransferase activity) are markedly increased in livers of rats treated with ␤-naphthoflavone or 4-methyl-5-pyrazinyl-3H-1,2-dithiole-3-thione (oltipraz). Nuclear runoff assays show that the effects of both inducers are primarily due to transcriptional activation. A 27-kilobase region that included the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 26 publications
(25 reference statements)
1
31
0
Order By: Relevance
“…Next, pairwise LD analysis was performed for the UGT1A genes using the polymorphisms detected in this study (1A8, 1A10, 1A9, 1A7, and 1A3) and previous studies (1A6, 1A4, 1A1, and common exons [2][3][4][5] 19-21 from the same 196 subjects, and the values for rho square (r 2 ), chi square (w 2 ), and |D 0 | were obtained. Variations found in only one subject were excluded from the analysis.…”
Section: Ld Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Next, pairwise LD analysis was performed for the UGT1A genes using the polymorphisms detected in this study (1A8, 1A10, 1A9, 1A7, and 1A3) and previous studies (1A6, 1A4, 1A1, and common exons [2][3][4][5] 19-21 from the same 196 subjects, and the values for rho square (r 2 ), chi square (w 2 ), and |D 0 | were obtained. Variations found in only one subject were excluded from the analysis.…”
Section: Ld Analysismentioning
confidence: 99%
“…2,3 The UGT1A N-terminal domains (encoded by the exon-1's) determine the substrate-binding specificity and the C-terminal domain (encoded by exons 2-5) is important for binding to UDP-glucuronic acid. 1 Thus, the exon 1 segments confer the substrate specificity of UGT1A isoforms, 4 and the 5 0 -flanking region (and possibly the 3 0 -flanking region) of each exon 1 is acknowledged to independently regulate the expression of each isoform. 3,4 A number of genetic polymorphisms including single nucleotide polymorphisms (SNPs) in UGT1As have been identified and published on the UDP glucuronosyltransferase home page (http://som.flinders.edu.au/FUSA/ClinPharm/UGT/allele_table.html).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of liver UGT1A7 mRNA is increased following treatment with 3-MC and oltipraz, similar to UGT1A6 mRNA in response to these chemicals. However, no analogous XRE or transcriptional elements mediating the regulation of UGT1A7 by 3-MC or oltipraz have been identified in the upstream promoter region (Metz and Ritter, 1998). It is possible that UGT1A7 is under the regulation of the XRE in the UGT1A6 promoter.…”
Section: Vansell and Klaassenmentioning
confidence: 99%
“…Analysis of the promoters of the human UGT1A1 and 1A6 genes showed that they were functional in liver and colon cells, respectively (8). Studies on the rat UGT1A6 and UGT1A7 genes have also shown that their promoter regions are capable of stimulating transcription in liver cells (9,10). In addition, UGT1A genes have recently been demonstrated to be induced by the nuclear receptors constitutive active receptor (CAR), aryl hydrocarbon receptor (AHR), pregnane X receptor (PXR) and peroxisome proliferator-activated receptor (PPAR) through binding to their promoter regions (9,(11)(12)(13)(14).…”
mentioning
confidence: 99%